Peran Lingkungan dan Pengalaman Proses Harapan dan Usaha dalam Pembentukkan Jati Diri - Marscelino Virgi Pratama; Edy Susanto; Alif Tegar Galih Khalefi; Yoga Bismoko Aptawidiyadhana (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Self-identity formation is essential to individual development and is influenced by social environments and life experiences. This study draws on Erikson's theory of psychosocial development and Bronfenbrenner's ecological theory of human development to understand how the interaction between the environment and individual experiences shapes identity formation in response to expectations and efforts. Social environments, such as family, friends, and community, provide a framework of values and norms that shape an individual’s initial identity, while personal experiences in managing expectations and efforts either reinforce or challenge this framework. The study concludes that balancing environmental support and experiential challenges enables individuals to develop a strong and flexible identity. The implications of this research highlight the importance of creating environments that support self-reflection and learning from experiences to foster healthy identity development.